The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pen.22077
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of addition curable silicone resins with excellent dielectric properties and thermal resistance

Abstract: A new addition curable silicone resin (ASiR) system with excellent dielectric and thermal properties was developed, which consists of only two components: poly(methylphenylvinylsiloxane) (PMPVSi) and an end‐capped hydrogen‐functionalized hyperbranched polysiloxane (EHFHPSi). PMPVSi is synthesized by a green and controllable process; EHFHPSi is first synthesized via A2 + B3 approach, and then end‐capped by hexamethyldisiloxane (HMDS). Three formulations were designed to investigate the optimum stoichiometry. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…By changing the formulation parameters, such as imbalance of the active functional groups, the molecular weight of the prepolymers, cross‐linker type, and filler addition, different network structures can be achieved . Among all parameters, the effect of stoichiometric imbalance on the network structure and on the corresponding mechanical or electrical performances already attracted substantial interest . However, to the best of our knowledge, the aspects of mechanical and electrical performances, which may in fact closely interrelate with each other through the polymer network structure, have mostly been investigated separately in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…By changing the formulation parameters, such as imbalance of the active functional groups, the molecular weight of the prepolymers, cross‐linker type, and filler addition, different network structures can be achieved . Among all parameters, the effect of stoichiometric imbalance on the network structure and on the corresponding mechanical or electrical performances already attracted substantial interest . However, to the best of our knowledge, the aspects of mechanical and electrical performances, which may in fact closely interrelate with each other through the polymer network structure, have mostly been investigated separately in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that DB values of VISR and ALSR are slightly higher than one of the traditional hyperbranched polymers. 20,36,37 This phenomenon may have resulted from the intramolecular cyclization of silanols in the process of random condensation polymerization so that it seems to increase the DB value.…”
Section: Methodsmentioning
confidence: 99%
“…In general, liquid silicone polymers can be solidified by the aid of three different curing mechanisms, namely, free radical coupling reaction, polycondensation, and hydrosilylation. Hydrosilylation is one of the key curing ways for preparing organosilicon materials in both industry and academia because this curing process proceeds at low temperature (60–150 °C) compared to the polycondensation type required for 200 °C and even more and can avoid the formation of bubbles and voids from volatile liberation that often occur in the conventional condensation process . Hydrosilylation cross-linking is an addition reaction between unsaturated bonds (e.g., CHCH 2 ) and silicon–hydrogen (Si–H) bonds derived from silicone polymers in the presence of a platinum complex catalyst (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…We report here our initial studies of MT copolymers, an obvious isomeric class of silicones (Figure a) that has been neglected in the literature for reasons that are not apparent. There are literature reports that use an MT resin as a component in more complex resins, report M-terminated silsesquioxane polymers, and characterize volatile MT oligomers by GCMS, as well as several patents that claim these isomeric materials; however, there is no literature that addresses the structure, or in particular, how to control the structure of these resins. Our interest in this isomer developed during recent studies with MQ copolymers, when it became apparent that the MT system would offer a much richer structural spectrum than can MQ.…”
Section: Introductionmentioning
confidence: 99%